2016
DOI: 10.1007/s10554-016-1004-z
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular relative wall thickness as a predictor of outcomes and of right ventricular reverse remodeling for patients with pulmonary hypertension

Abstract: Mid-term right ventricular (RV) reverse remodeling after treatment in patients with pulmonary hypertension (PH) is associated with long-term outcome as well as baseline RV remodeling. However, baseline factors influencing mid-term RV reverse remodeling after treatment and its prognostic capability remain unclear. We studied 54 PH patients. Mid-term RV remodeling was assessed in terms of the RV area, which was traced planimetrically at the end-systole (RVESA). RV reverse remodeling was defined as a relative dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
1
15
0
4
Order By: Relevance
“…Results of off-line readings were forwarded to an external contract research organisation in order to merge with the clinical data of the riociguat trials. A clinically significant improvement of right heart size was defined as a ≥ 15% reduction RA or RV area [12].…”
Section: Methodsmentioning
confidence: 99%
“…Results of off-line readings were forwarded to an external contract research organisation in order to merge with the clinical data of the riociguat trials. A clinically significant improvement of right heart size was defined as a ≥ 15% reduction RA or RV area [12].…”
Section: Methodsmentioning
confidence: 99%
“…The high afterload then leads to further CO reduction and compensatory RV dilation, while maladaptive RV remodeling causes further thinning due to wall stretching, resulting in a vicious cycle and RV dysfunction. Our group recently reported that RV‐RWT is an independent parameter for predicting mid‐term RV reverse remodeling, and is associated with long‐term posttreatment survival of PH patients . Moreover, incremental changes in RV‐RWT proved to be of significant value for prediction of survival, and the combined assessment of RV‐RWT and mid‐term RV reverse remodeling resulted in more accurate prediction of outcome for PH patients.…”
Section: Discussionmentioning
confidence: 96%
“…Standard echocardiographic measurements were obtained according to the current guidelines of the American Society of Echocardiography/European Association of Cardiovascular Imaging . In addition, the assessment of RV relative wall thickness (RV‐RWT) was calculated from RV free wall thickness/basal RV linear dimensions at end‐diastole according to the current guidelines of the American Society of Echocardiography/European Association of Cardiovascular Imaging . Digital data were transferred to dedicated offline software (EchoPAC version BTO8; GE Vingmed Ultrasound AS) for subsequent offline speckle‐tracking analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly prior studies have demonstrated RV size and function to be a critical prognostic indicator in pulmonary arterial hypertension (PAH) and congenital heart disease. 7,8,9,10 Despite the role of the RV in stratification of prognosis, non-invasive evaluation of the RV remains challenging due to several key anatomic factors.…”
Section: Right Ventricle Backgroundmentioning
confidence: 99%